Hydrogen production activity of MoS2-ZnIn2S4 nanocomposite under visible light irradiation. (2022) - Chand, Mool; Rawat, A.S.; Khanuja, Manika; Rawat, Seema
Abstract: In this manuscript, we report the synthesis of MoS2 -ZnIn2 S4 nanocomposite by using methods including hydrothermal and chemical aqueous method under low temperature. The prepared MoS2 -ZnIn2 S4 composite sample was characterized by X-ray powder diffraction (XRDfield emission scanning electron microscopy (FESEM). The photocatalytic activities for H2 production were investigated under the visible light of MoS2 -ZnIn2 S4 nanocomposite. The result indicates that H2 production rate of ZnIn2 S4 increase by adding of MoS2 as co-catalyst and MoS2 -ZnIn2 S4 nanocomposite show higher rate of hydrogen production under. pure ZnIn2 S4 sample shows a very low rate of H2 production activity (30 μ mol. g -1 h −1 ) however MoS2 /ZnIn2 S4 composite shows approximately 3 times higher rate of H2 production activity (97.36 μ mol. g -1 h −1 . The synergistic combination of increased specific surface area, efficient electron hole pair separation, and amplified catalytic active sites is primarily responsible for the increased rate of H2 production activity. This work contributes a high potential of developing of low cost and low temperature or template free synthesised semiconductor for hydrogen production.